Increased Surgical Duration Associated With Prolonged Hospital Stay After Isolated Posterior Cruciate Ligament Reconstruction - Swindell HW; Boddapati V; Sonnenfeld JJ; Trofa DP; Fleischli JE; Ahmad CS; Popkin CA (Dove Medical Press, 2019)
Hasani W Swindell,1 Venkat Boddapati,1 Julian J Sonnenfeld,1 David P Trofa,1 James E Fleischli,2 Christopher S Ahmad,1 Charles A Popkin1 1Department of Orthopedic Surgery, Columbia University Medical Center, New York, NY, USA; 2Shoulder and Elbow Center, OrthoCarolina Sports Medicine Center, Charlotte, NC, USACorrespondence: Charles A PopkinDepartment of Orthopedic Surgery, Columbia University Medical Center, 622 West 168th Street, PH – 11, New York, New York 10032, USATel +1 212-305-4787Email cp2654@columbia.eduPurpose: Although often performed using a variety of reconstructive techniques and strategies, no clinically significant differences presently exist between the approaches available for isolated PCL reconstructions. Given the operatively challenging nature of these procedures, there lies a potentially increased risk of postoperative complications and healthcare expenditures. Our investigation sought to identify patient and surgical risk factors associated with prolonged hospital stays following isolated PCL reconstruction and determine the incidence of 30-day complications after PCL reconstruction using the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database.Method: Patients undergoing isolated PCL reconstructions between 2005 and 2016 were identified in the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database using Current Procedural Terminology codes. Baseline patient and operative characteristics were evaluated as possible risk factors for overnight hospital admissions following PCL reconstruction and analyzed using multivariate analyses.Results: A total of 249 patients were identified. Multivariate analyses demonstrated that increased operative duration >120 mins (OR 5.04, CI 2.44–10.40; p <0.001) was associated with an increased risk of overnight hospital stay. Major complications occurred in 0.4% (N=1), and minor complications occurred in 0.8% (N=2) with overall complications occurring in 1.2% (N=3) of all patients. Wound dehiscence was the only major complication while superficial surgical site infection and deep vein thrombosis were the only minor complications. 34.1% (N=85) of patients required an overnight hospital stay postoperatively.Conclusion: Surgical duration >120 mins carried an increased risk of overnight hospital stay after isolated PCL reconstructions. As there are presently minimal significant clinical differences between current PCL reconstruction techniques, improved surgeon familiarity and comfort with a single technique is recommended to decrease operative time and avoid prolonged hospital stays and healthcare expenditures.Level of evidence: III, retrospective comparative study.Keywords: operative time, overnight hospital stays, healthcare expenditures, American College of Surgeons National Surgical Quality Improvement Program, NSQIP